Women Do it Better: An Investigation on the Association between Gender Diversity In Board of Directors and the Financial Performance - Rossi, Matteo; Galasso, Serena; Capasso, Arturo (International Journal of Economics and Financial Issues, 2017)
The aim of this study is to analyse the impact of gender diversity on the financial performance of Italian listed companies. A cross-sectional regression used about the data of the year 2016 of Italian listed firms. The study is a mix of descriptive and explanatory research. The model is a scoring model, composed by two variables: Board of Directors (BoD), and Top Management (TM). We investigate the impact of these variables on the Return on Equity, the Price book value, and the EBITDA. The study shows a positive relationship between financial performance and the composition of the BoD and the operational performance and the composition of the Top management. The cross sectional regression highlights also the non-relation on the Return on Equity. Anyway these contrasting results confirm the properness of the model for this kind of research. Keywords: Gender Diversity, Financial Perfomance, Borad of Directors, Italian Listed Companies JEL Classifications: G32, M14, G30